Full-body Movement in Numerical Trainings: A Pilot Study with an Interactive Whiteboard - Ursula Fischer; Korbinian Moeller; Stefan Huber; Ulrike Cress; Hans-Christoph Nuerk (Serious Games Society, 2015)
In this pilot study, we introduce an effective spatial-numerical training to improve children's arithmetic abilities. We designed this training based on previous successful trainings of spatial-numerical associations (such as number line estimation) and introduced a full-body response movement. Children responded to a number line estimation task presented on an interactive whiteboard by moving their whole body to the left or right. In a pilot study with a small group of children (total sample size N = 27), this experimental training was compared to two control trainings, one training the same task without the full-body movement and one training a different task with full-body movement. The experimental training led to significant improvement in all dependent measures and was most effective in enhancing performance in a spatial-numerical task. Furthermore, full-body movement helped children maintain their performance level in multi-digit addition. We conclude that full-body movement can enhance the efficiency of numerical trainings, which could also be successfully utilized in serious games and incorporated into the classroom.